Cultivating Constructivism: Inspiring Intuition and Promoting Process and Pragmatism. Issue 1 (2nd January 2016) - McWilliams, Spencer A.
Abstract : Given the compelling strength of its theory, research, and practice, why does constructivism remain at the fringes of our field rather than comprising the mainstream? Constructivism assumes that humans create knowledge in ever-changing contexts, rather than the more common view that nature reveals to us its own innate, foundational "way that it is" that confers meaning to us. Acknowledging the human desire for certainty might inform our response to our critics. We might understand individuals' choices between these two views as based on intuition, temperament, and core beliefs that determine whether one accepts dominant discourses or seeks alternatives. Advancing and fostering constructivism might benefit from appealing to the latter population. Two approaches might assist in that appeal. First, we might actively embrace a process view of ontology that comprehends phenomena in terms of interrelated, changing relationships rather than a container of fixed entities with innate permanent characteristics. Second, we might reaffirm the merits of American pragmatist philosophy, the foundation of constructivist psychology, demonstrating its current relevance by considering second- and third-generation contemporary pragmatists who emphasize the fundamentally human role in knowledge creation. Finally, I suggest that because the discipline of psychology studies how living organisms create knowledge, it could assume a greater role as the foundation of all disciplines.